THE EFFECT OF PUBLIC SERVICE QUALITY ON COMMUNITY SATISFACTION IN THE ANALYSIS OF SYSTEMATIC LITERATURE REVIEW - Ningrum, Adinda Puspita; Wicaksana, Ricko Adi (DIA: Jurnal Administrasi Publik, 2024)
The level of public satisfaction is a benchmark for assessing the quality of public service delivery in a country. In this study, the five dimensions of service quality include tangibles, reliability, responsiveness, assurance, and empathy. This study examines the relationship between public service quality as the independent variable and community satisfaction as the dependent variable. In more detail, service quality is broken down into five dimensions that eventually become separate dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. Using the systematic literature review method, studies published from 2018 to 2023 were analyzed. In determining the inclusion and exclusion criteria for studies obtained from the database, this study used the criteria of population, intervention, comparator, and type of study. This research found that ten of the 17 studies reviewed stated that the five dimensions of quality partially affect public satisfaction. This research limited the studies to public agencies including ministries or agencies, functional departments, specialized agencies, and state-owned enterprises (SOEs).